Factors influences buying house decision towards Generation Y’s in Malaysia - Md Yatim, Nor Farhanah (2021)
The main purpose of the study is to identify the factor influencing house decision among Generation Y in Malaysia. In this research, the most concern part of this study which is the factors that researcher want to identify is Property Attribute, Property Surrounding and Property View. This study also was an attempt to observe the factors that influence the relationship between property attribute, property surrounding and property view toward the factor influencing house buying decision among Generation Y in Malaysia. Basically, Generation Y is a group born between 1980 and 2005. The method used in this research was causal research or hypothesis testing in the experiment, and non-probability sampling had been used and to be more accurate, judgement sampling was used. Other than that, this study analysis relates to primary and secondary data for supporting the sampling technique. Meanwhile, the researcher uses the questionnaire which is primary data as a method to gather all data from the survey of respondents in order to meet the objectives of this research. The data was collected and analysed by 70 respondents using the Statistical Package for Social Science (SPSS). Moreover, the analysis of descriptive, reliability and regression was also included in this research. This study can be seen as a foreword to a more comprehensive study that could be carried out by future research into this topic. There are a few recommendations to propose beneficial suggestions and to call for further research and studies. Lastly, we hope that this study will cover the gap in understanding the importance of the factors that influence house buying decisions among Generation Y, especially in Malaysia.